Climate Change—National and International Scenario - Verma, Pushp Lata (SCHOOL SCIENCE, 2025)
India's per capita H emission (2.33t CO2e) is 1/3 of the world average (6.76) and is very low compared to developed countries, as well as, many of the devoloping countries. Around 55 per cent of India’s population still does not have access to commercial energy. In the energy sector, some of the specific initiatives taken by India include introduction of Compressed Natural as (CN) for public and private transport in metropolitan areas. A great emphasis has also been laid on the development of alternate fuel, namely hydrogen and biofuel. Recently, a decision has been taken to promote desert as a hub for renewable energy by establishing a Solar City in the Thar desert area. Besides, steel, aluminium, fertilisers, paper, cement are some of the major energy-intensive sectors where India’s energy efficiency has attained the global standards.